Dimensional Stability of Plywood Panels Made from Thermally Modified Poplar Veneers in the Conditions of Variable Air Humidity - Vladislav Zdravković (University of Zagreb, Faculty of Forestry and Wood Technology, 2013)
Some properties of plywood panels made from untreated and thermally modified (90 min. at 200 ºC) poplar veneers and their combinations have been analyzed. The change in equilibrium moisture content and the change in dimensions of the samples conditioned above water in closed containers were examined. The analysis using F-test (ANOVA) at the significance level of 95% confirmed that, regarding moisture content, all combinations of plywood panels differed significantly from the control panels. However, the analysis of thickness swelling showed that there was no significant difference among the plywood panels of similar construction. The highest values of anti-swelling efficiency were shown by plywood panels made from thermally modified veneers.